PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LIVEWORKSHEETS PADA MATERI LISTRIK DINAMIS DI MTS BINA POTENSI SIS ALJUFRI - Magvira, Magvira; Arda, Arda; Ardiansyah, Ardiansyah (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
This research is a development research which aims to develop learning media based on Liveworksheets on dynamic electricity material at MTs Bina Potential Sis Aljufri. The research subjects were students of class VIII MTs Bina Potential Sis Aljufri. The development model used is the ADDIE development model. The analysis technique was carried out using quantitative descriptive data analysis techniques, material expert validation, media expert validation and student response questionnaires. The results showed that the validity aspect of Liveworksheets-based learning media products developed by the authors obtained an average score of 3.45 with a percentage of 86.25% from material experts who included very good criteria, an average score of 3.00 with a percentage of 75% from media experts including good criteria. In the practicality aspect, an average score of 3.28 was obtained with a percentage of 82.48% from the results of the responses of students in small-scale field trials, where the level of practicality was included in the high practicality level. The use of Liveworksheets-based learning media can make it easier to understand the material presented and can foster students' interest and learning motivation.